Problematika Pelayanan Bimbingan Manasik Haji Sepanjang Tahun di Pusat Layanan Haji dan Umrah Terpadu kota Padang - Efrizal Ef Syarif; Nazirman Nazir Man; Abdul Manan Sihombing (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2021)
This research describes information on various issues of Hajj Manasik Guidance activities throughout the year at the Integrated Hajj and Umrah Service Center (PLHUT) Padang City. This activity is an innovation from the Ministry of Religion of the Republic of Indonesia since 2019 which aims to meet the achievement of the objectives of organizing the Hajj, providing guidance, service and protection for pilgrims in accordance with sharia, as well as realizing independence and resilience in the implementation of the Hajj and Umrah pilgrimages. The Facts show that this new innovation creates some problems for PLHUT that require solutions. The research aims to find out the problems and solutions provided in dealing with the problem of guidance. This research is a field research with a descriptive qualitative approach. The data source is taken from the Head of the Hajj and Umrah Organizing Section of the Ministry of Religion of the city of Padang, implementing officers, supervisors and prospective pilgrims as well, by using purposive technique. The instruments that used are observation and interview. The results are as following : 1) The problems faced by PLHUT were budget issues, guidance materials, Jamaat do not have the maximum time to follow the guidance, the available time allocation and limited facilities. Presentation of guidance material and its schedule are less systematic and module are ineffective. 2) PLHUT provides a solution by increasing the guidance time in “Ramadan” every day, the committee will provide a schedule and guidance module.